Sobre os efeitos do interacionismo no diagnóstico de linguagem - Lúcia Arantes (Cadernos de Estudos Lingüísticos, 2011)
This paper discusses the influence of Cláudia de Lemos’s reflection on language and language acquisition for the circumscription of the notion of diagnosis in the field of language/speech therapy. I argue that most speech pathologists who have approached the above mentioned author’s works made such a movement in a naïve and equivocal way. In this article, I endeavor, after the critical review presented, to suggest an alternative proposal for diagnosis that emphasizes my theoretical commitment to a specific language theory which allows for the consideration of pathological/symptomatic speech.